[3+2] Cycloaddition to a Chiral 5-Methylene-1,3-dioxolan-4-one and Pyrolysis of the Spiro Adducts - R. Alan Aitken; Lynn A. Power; Alexandra M. Z. Slawin (Molecules)
The [3+2] cycloaddition chemistry of (2S)-5-methylene-2-t-butyl-1,3-dioxolan-4-one, derived from lactic acid, has been examined, and spiro adducts have been obtained with benzonitrile oxide, acetonitrile oxide, diazomethane and diphenyldiazomethane. The structure and absolute stereochemistry of the benzonitrile oxide adduct has been confirmed by X-ray diffraction, and all the adducts have been fully characterised by 1H and 13C NMR. Attempted cycloaddition with a nitrile sulfide, a nitrile imine and azides failed. Pyrolysis results in a range of novel gas-phase reactions, with the nitrile oxide adducts giving pivalaldehyde, CO2, the nitrile and ketene, the diazomethane adduct losing only N2 to give a cyclopropane-fused dioxolanone, and the diphenylcyclopropane derived from diphenyldiazomethane giving mainly benzophenone in a sequence involving the loss of pivalaldehyde and methyleneketene.